Assessment of the Use of Capital Appraisal Techniques in Real Assets Investment Decisions by MSMEs in Northwest Geo-political Zone, Nigeria - Ogbulu, Onyemachi Maxwell; Udensi, C. E.; Okanta, S. U.; Uruakpa, P. C.; John, Onoh; Ndubuisi, Paul (Archives of Business Research, 2025)
While it is generally agreed that MSMEs are critical to the economic development of every nation, the actualization of this strategic goal has remained very elusive to developing countries in particular. Like other developing economies, Nigeria has continued to grapple with the challenges of effectively harnessing the potentials of MSMEs. Beyond the problems attendant to the controversies surrounding MSMEs, the lingering stakeholder dissatisfaction with the performance of MSMEs calls to question the effectiveness of the numerous policy reforms focused on the MSME ecosystem. Unfortunately, the policy reforms have been criticized for giving more emphasis to funding and ease of doing business and less to managerial competencies of MSME operators. The study focused on the level of awareness and adoption of appraisal techniques in making real asset investment decisions by MSME operators and the degree to which socio-economic factors influence MSMEs investment in real physical assets in Nigeria. Based on explanatory and cross-sectional survey, data were sourced from 750 MSMEs located in the capital cities of five Northwest states of the country. While descriptive statistics were used in analysing the data, the hypotheses were tested with multinomial logistics and generalized linear models. Findings of the study revealed that operators of MSMEs showed low level of awareness and adoption of investment appraisal techniques with payback period and accounting rate of return being the dominant techniques. In addition, increase in tax and insecurity showed positively significant but low effect on MSMEs’ investment in real physical assets. These findings clearly point to the lack of managerial competencies necessary for the embrace and effective adoption of rational methods of decision making by operators of MSMEs. This, therefore calls for a special policy focus on the development of the managerial capacities of operators of MSMEs. In addition, TETFUND should, in collaboration with NUC, sponsor universities to develop a dynamic business directory of MSMEs in their locality in addition to providing free business development services to a given number of them on annual basis.